2008
DOI: 10.1128/jcm.00400-08
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of the Hospital Environment with Gastroenteric Viruses: Comparison of Two Pediatric Wards over a Winter Season

Abstract: The aims of this study were to examine the extent of gastroenteric virus contamination in a pediatric primary immunodeficiency (PPI) ward and a general pediatric ward over a winter season and to determine whether changes to hospital infection control interventions would have an impact on environmental contamination levels within pediatric units. Environmental swabs were collected weekly from 11 sites in both wards from 15 December 2005 to 3 March 2006 and examined for the presence of norovirus (NoV), astroviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…Contamination of environmental surfaces, such as sanitary equipment, scales, or objects in the examination room, is known to play a role in norovirus transmission [25,26]. Therefore, hospitalized symptomatic patients with proven norovirus infection are usually isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of environmental surfaces, such as sanitary equipment, scales, or objects in the examination room, is known to play a role in norovirus transmission [25,26]. Therefore, hospitalized symptomatic patients with proven norovirus infection are usually isolated.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated previously, enteric viruses have been shown to maintain infectivity on surfaces over prolonged periods. Human noroviruses have been detected on a variety of surfaces including cellular phones, public phones, televisions, chairs, keyboards, microwave ovens, bathroom light switches, various handles and knobs of kitchen and bathroom items, bed frames, and chairs (Boxman et al, 2011;Gallimore et al, 2006Gallimore et al, , 2008. Boxman et al (2011) reported year round prevalence of hNoVs on environmental surfaces of catering facilities even without a recently reported outbreak of acute gastroenteritis.…”
Section: Enteric Virus Transmission Due To Environmental Surface Contmentioning
confidence: 99%
“…The exposure occurs through touch and transfer of pathogens present on the fomite to the hands and then to the mouth, nasopharynx, and eyes (Abad et al, 1994(Abad et al, , 2001Carducci et al, 2011;Herzog et al, 2012). The detection of viruses on a large variety of surfaces and fomites, such as tables, door knobs, walls, toilets seats, thermometers, gloves, among others (Boone and Gerba, 2007;Ganime et al, 2012) has helped to demonstrate this route of transmission in sporadic cases and also in outbreaks (Ansari et al, 1988(Ansari et al, , 1991Gallimore et al, 2004Gallimore et al, , 2005Gallimore et al, , 2006Gallimore et al, , 2008Wu et al, 2005;Boxman et al, 2009). However, the method for recovering viruses from surfaces is not an easy task, mainly due to its heterogeneous distribution, as well as the low viral load and the eventual presence of inhibitors in these surfaces (Rodríguez-Lázaro et al, 2012).…”
Section: Discussionmentioning
confidence: 93%